Determination of Uranium Series Activity Before Secular Equilibrium Is Established. Issue 4 (October 2019) - Wilson, Charles A.; Matthews, Kenneth L.; Hamideh, Amin M.; Wang, Wei-Hsung
Abstract : Abstract: Timely achievement of uranium series' secular equilibrium is not always feasible. Our objective is to mathematically justify methods for early uranium series gamma spectroscopy measurements that can accurately predict naturally occurring radioactive material equilibrium activities long before equilibrium is established. It was believed that, regardless of prior 222 Rn escape, after sealing a sample for a few hours the activities of 222 Rn, 226 Ra, and 238 U could theoretically be determined with a single measurement of both 214 Pb and 214 Bi. However, when accounting for error, this theory did not work as expected (CV = 14.0 in 226 Ra simulation). A similar approach published by Li et al. in 2015 proved to be much more reliable with the error considered, using 214 Pb activities measured at two different times gave significantly improved results when tested the same way (CV = 0.29 in 226 Ra simulation). Because both 214 Pb and 214 Bi activities are typically available when using gamma spectrometry, we combine these approaches and further increased the accuracy of the calculated activities (CV = 0.21 in 226 Ra simulation).